 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
A body is thrown up wuth initial velocity 'u' .and reaches height 'h' To reach double height it must be projected with initial velocity of-

```
9 years ago

```							 if the particle is projected with velocity u then at maximum height its velocity becomes 0
we have ,
V2 = U2 - 2gHmax
U2 = 2gHmax                or
U2 directly  proportional to Hmax
(Ui)2 / (Uf)2 = (Hmax)i/(Hmax)f
Ui = u , Uf=? , (Hmax)i = h , (Hmax)f = 2h
after substituting these
Uf = (sqrt2)u        ans

```
9 years ago
```							the height attained by the body is h therefore applying third equation of motion
v^2=u^2-2gh
at height h final velocity is zero
u^2=2gh
u=square root(2gh) ....1
now height attained by the body is 2h
therefore putting 2h in place of h
the equation comes to be
u'^2=2g(2h)
u'= square root(2*2gh)
but square root 2gh=u
therefore u'=u*square root(2)

```
9 years ago
```							it is given that 'h' height is attained by a body and its velocity is u...
writing eqn of motion...
v(sqr)-u(sqr)=2as
putting values....
v=0,u=u,and a=-g(coz g is in downward direction), s=h
-u(sqr)=2(-g)h
u(sqr)=2gh
so to get height of 2h u should be sqrroot(2) to satisfy above eqn

```
9 years ago
```							root 2 times the original velocity
```
9 years ago
```							It is sqrt 2 times u.
```
9 years ago
```							sqrt of usqr+2gh derivation please
```
6 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on General Physics

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 18 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions